Should we embed randomized controlled trials within action research: arguing from a case study of telemonitoring. Issue 1 (December 2016) - Day, Karen; Kenealy, Timothy; Sheridan, Nicolette
Abstract Background Action research (AR) and randomized controlled trials (RCTs) are usually considered to be theoretically and practically incompatible. However, we argue that their respective strengths and weaknesses can be complementary. We illustrate our argument from a recent study assessing the effect of telemonitoring on health-related quality of life, self-care, hospital use, costs and the experiences of patients, informal carers and health care professionals in two urban hospital services and one remote rural primary care service in New Zealand. Methods Data came from authors' observations and field notes of discussions with three groups: the healthcare providers and healthcare consumers who participated in the research, and a group of 17 researchers and collaborators. The consumers had heart failure (Site A, urban), airways disease (Site B, urban), and diabetes (Site C, rural). The research ran from 2008 (project inception) until 2012 (project close-off). Researchers came from a wide range of disciplines. Both RCT and AR methods were recognised from early in the process but often worked in parallel rather than together. In retrospect, we have mapped our observed research processes to the AR cycle characteristics (creation of communicative space, democracy and participation, iterative learning and improvement, emergence, and accommodation of different ways of knowing). Results We describe the context, conduct and outcomes of the telemonitoring trial, framing the overall process in the language of AR. Although not fully articulated at the time, AR processes made the RCT sensitive to important context, e.g. clinical processes. They resulted in substantive changes to the design and conduct of the RCT, and to interpretation and uptake of findings, e.g. a simpler technology procurement process emerged. Creating a communicative space enabled co-design between the researcher group and collaborators from the provider participant group, and a stronger RCT design. Conclusions It appears possible to enhance the utility of RCTs by explicitly embedding them in an AR framework to shape stronger RCT design. The AR process and characteristics may enable researchers to evaluate telehealth while enhancing rather than compromising the quality of an RCT, where research results are returned to practice as part of the research process. Trial registration Australian New Zealand Clinical Trials Registry, referenceACTRN12610000269033 .